2011
DOI: 10.4103/2152-7806.85607
|View full text |Cite
|
Sign up to set email alerts
|

"Real-world" comparison of non-invasive imaging to conventional catheter angiography in the diagnosis of cerebral aneurysms

Abstract: Background:Based on numerous reports citing high sensitivity and specificity of non-invasive imaging [e.g. computed tomography angiography (CTA) or magnetic resonance angiography (MRA)] in the detection of intracranial aneurysms, it has become increasingly difficult to justify the role of conventional angiography [digital subtraction angiography (DSA)] for diagnostic purposes. The current literature, however, largely fails to demonstrate the practical application of these technologies within the context of a “… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 23 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…The sensitivity and specificity of noninvasive CTA/MRA imaging in the detection of UIA have been previously described in the literature. [ 3 5 8 10 11 12 13 14 17 18 19 ] This data is variable and sometimes even contradictory as a result of varied quality of noninvasive imaging. An earlier meta-analysis reported that the accuracy of CTA/MRA is about 90%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensitivity and specificity of noninvasive CTA/MRA imaging in the detection of UIA have been previously described in the literature. [ 3 5 8 10 11 12 13 14 17 18 19 ] This data is variable and sometimes even contradictory as a result of varied quality of noninvasive imaging. An earlier meta-analysis reported that the accuracy of CTA/MRA is about 90%.…”
Section: Discussionmentioning
confidence: 99%
“…The differences in the detection of UIA by DSA as compared to MRA and CTA have been previously documented by studies that focused primarily on the overall accuracy and reliability of detection, rather than on FP findings in current practice. [ 11 13 14 ] Since the follow-up of patients with untreated UIA involves serial imaging, eliminating FPs diagnosed noninvasively is essential. In this retrospective study, we aimed to determine if there is still a diagnostic role for DSA in patients referred with UIA detected by noninvasive imaging in the current era.…”
Section: Introductionmentioning
confidence: 99%
“…MR angiography (MRA) has several advantages over CTA including the lack of radiation exposure and a high sensitivity up to 93% even for the aneurysms less than 3 mm. 10 Some limitations of MRA include the longer acquisition time and greater likelihood of motion and other artifacts. 8 The high sensitivity and absence of radiation make MRA a preferred imaging study for the outpatient evaluation of cerebral aneurysms at many centers.…”
Section: Discussionmentioning
confidence: 99%